Psychoanalysis and wisdom: encountering 'Ethics of the Fathers' - Marcus, Paul (Routledge, 2024)
"Psychoanalysis and Wisdom applies psychoanalytic insights to one of the great examples of wisdom literature, the Ethics of the Fathers, an ethical tractate of the Talmud. Paul Marcus quotes key passages from the Ethics of the Fathers, providing a psychoanalytic commentary to enlarge and deepen our understanding of its contents and focusing primarily on what constitutes a flourishing life. Marcus then considers what psychoanalysis can provide in its engagement with this classic of the wisdom teachings, such as illuminating aspects of the Ethics that are overlooked or underappreciated, and how "pearls of wisdom" from the Ethics can be incorporated into psychoanalytic theory and practice. The book contains clinical material as well as the insights of philosophers like Martin Buber, Gabriel Marcel, and Emmanuel Levinas. Psychoanalysis and Wisdom will appeal to readers interested in psychoanalysis and psychotherapy and to academics and students of psychoanalytic studies, religious studies, Judaic studies, and philosophy"--